2022
DOI: 10.3390/ijms23168889
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of Carbon-Based Nanomaterials, Starring Phagocytes

Abstract: In the field of science, technology and medicine, carbon-based nanomaterials and nanoparticles (CNMs) are becoming attractive nanomaterials that are increasingly used. However, it is important to acknowledge the risk of nanotoxicity that comes with the widespread use of CNMs. CNMs can enter the body via inhalation, ingestion, intravenously or by any other route, spread through the bloodstream and penetrate tissues where (in both compartments) they interact with components of the immune system. Like invading pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 173 publications
0
5
0
Order By: Relevance
“…The toxicity of GDMs on myeloid cells is still a matter of debate 33 . Some authors have reported the so-called “mask effect” to explain cell toxicity induced by GDMs 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity of GDMs on myeloid cells is still a matter of debate 33 . Some authors have reported the so-called “mask effect” to explain cell toxicity induced by GDMs 34 .…”
Section: Resultsmentioning
confidence: 99%
“…roughness and, more pronouncedly, redox state) also modulate differently BM-MDSC viability. The toxicity of GDMs on myeloid cells is still a matter of debate 33 . Some authors have reported the so-called "mask effect" to explain cell toxicity induced by GDMs 34 .…”
Section: The Physico-chemical Differences Of Rgo Substrates Different...mentioning
confidence: 99%
“…To this regard, the toxicity of GDMs on myeloid cells is still a matter of debate. 41 Some authors have reported the so-called “mask effect” to explain cell toxicity induced by GDMs. 42 Specifically, the close contact between GO nanosheets and cell membranes could drive to GO internalization.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between co-existing pollutants and their resulting combined toxicity is a research frontier in environmental toxicology (Svadlakova et al, 2022;Wang et al, 2023). MWCNTs have been shown to adsorb DBP through π-π interactions, and thus form complexes in the environment (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%